Durability of zirconia and lithium disilicate crowns in bruxism patients: a systematic review - Juwita Raditya Ningsih; Jaya Ria Rezky (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Fatigue stress carried on by repetitive occlusal loads that fail to recover teeth, as in bruxism cases, can weaken and lower the material's strength. Patients with bruxism receive dental care to minimize biological costs while halting further tooth loss and restoring function and attractiveness. It has been difficult to combine the aesthetic appeal and strength of the restorative materials up to this point. The purpose of the review article is to determine how durable dental crown materials are in patients with bruxism so that this can be considered when selecting crown materials.Method: This literature review follows the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). During the search and selection process, studies were selected using the framework (P), Intervention (I), Comparison (C), Outcomes (O), and Study design (S; PICOS): (P): Patients treated with crowns; (I): crown in bruxism patient; (C): type of crown material (O): Main results are: outcome of crown use in bruxism patients (S): Randomized controlled trial (RCT), cohort studies, prospective studies, and case series were included.The data search process via: (PubMed), Google Scholar, Scopus, and Science Direct, is limited to 2018-2024. The keywords used are (bruxism OR